The Effect of Buerger Allen Exercise Towards Physical Health Performance of Peripheral Neuropathy Patients - Qomariah, Siti Nur; Lin, Chueh-Ho (Universitas Airlangga, 2023)
Introduction: Peripheral neuropathy is a common microvascular complication in Diabetes Mellitus patients, with symptoms of tingling, numbness, pain in the feet, and disabilities in daily activities. Buerger Allen Exercise to stimulate the development of collateral circulation in the feet. The purpose of the study was to explain the effect of Buerger Allen's Exercise on the physical health performance of diabetic neuropathy patients. Methods: The research design used an experimental one-group pre-test post-test design. Purposive sampling technique with inclusion criteria: male and female DM patients, with a long history of diabetes> 5 years, undergoing treatment at the health center / other health services. Samples were taken in Krembangan Surabaya City with as many as 24 respondents. The independent variable was the Buerger Allen Exercise. The dependent variables were the physical health performance of diabetic neuropathy patients (peripheral oxygen saturation (StO2), Ankle-Brachial Index (ABI on the foot), and physical activity ability). The instruments used were an observation sheet for measurements of StO2, ABI, and physical ability. The research data were analyzed using the Paired t-test statistical test with a significance level of p <0.05. Results: There are significant results Buerger Allen Exercise of Ankle-Brachial Index (p=0.0085) and physical activity ability (p=0.031), and no significant result of peripheral oxygen saturation (p=0.075). Conclusion: There is an effect of the Buerger Allen Exercise on the Ankle-Brachial Index and physical activity ability of diabetic neuropathy patients. Further research needs to examine Buerger's exercise toward blood glucose levels and control factors that are related.